Diarrhea as a Prognostic Factor for Severe COVID-19 - Dinda Nisrina; Hasan Maulahela (The Indonesian Society for Digestive Endoscopy, 2022)
In March of 2020, the WHO has declared the state pandemic of COVID-19 that started in the city of Wuhan, China. The widespread of cases resulted in 2,877,476 cases and 73,582 death reported in Indonesia. It is commonly known that the respiratory system was the main problem in COVID-19, but it is recently reported that gastrointestinal involevment has a higher likelihood to develop into severe cases. Moreover, it is found that diarrhea is the most highly prevalent of the gastrointestinal signs and symptoms in COVID-19 patients. The aim of this evidence-based case report is to understand the association between diarrhea and severe cases of COVID-19. A search on Pubmed, Scopus and Cochrane result in five articles to be appraised using Centre for Evidence-Based Medicine (CEBM) critical appraisal tool. The most recent systematic review by Ghimere S et al (2020), found COVID-19 patients with diarrhea has higher likelihood of developin ginto a severe case (OR = 1.63, 95% CI: 1.11 – 2.38). While the cohort studies showed several prognostic factors that may potentially effect the outcome of severe COVID-19 cases. It is concluded that severe COVID-19 cases were more likely to be found in patients presenting with diarrhea. Thus, Confirmed COVID-19 patients with diarrhea should be carefully evaluated to anticipate worsening of symptoms.